Occupation and use of a marginal landscape (Scottish Historical and Archaeological Internet Reports, 2005)
In the introduction it was suggested that the existing archaeological record for Arisaig supports the identification of a core area of permanent settlement from as early as the Bronze Age, surrounded by peripheral areas of less-intensively exploited land. The data collected in the course of the A830 investigations support this model, with relevant evidence coming both from site-specific archaeological studies and the landscape-scale palaeo-environmental study. The evolution of the Arisaig landscape is described chronologically from the early prehistoric period through to the recent past.